Application of Mechanical Ventilation Weaning Predictors After Elective Cardiac Surgery - Silva,Mayara Gabrielle Barbosa e (2015)
ABSTRACT OBJECTIVE: To test several weaning predictors as determinants of successful extubation after elective cardiac surgery. METHODS: The study was conducted at a tertiary hospital with 100 adult patients undergoing elective cardiac surgery from September to December 2014. We recorded demographic, clinical and surgical data, plus the following predictive indexes: static compliance (Cstat), tidal volume (Vt), respiratory rate (f), f/ Vt ratio, arterial partial oxygen pressure to fraction of inspired oxygen ratio (PaO2/FiO2), and the integrative weaning index (IWI). Extubation was considered successful when there was no need for reintubation within 48 hours. Sensitivity (SE), specificity (SP), positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+), and negative likelihood ratio (LR-) were used to evaluate each index. RESULTS: The majority of the patients were male (60%), with mean age of 55.4±14.9 years and low risk of death (62%), according to InsCor. All of the patients were successfully extubated. Tobin Index presented the highest SE (0.99) and LR+ (0.99), followed by IWI (SE=0.98; LR+ =0.98). Other scores, such as SP, NPV and LR-were nullified due to lack of extubation failure. CONCLUSION: All of the weaning predictors tested in this sample of patients submitted to elective cardiac surgery showed high sensitivity, highlighting f/Vt and IWI.